Effects of surgery on the cancer stem cell niche. Issue 3 (March 2016) - O'Leary, D.P.; O'Leary, E.; Foley, N.; Cotter, T.G.; Wang, J.H.; Redmond, H.P.
Abstract: Recent identification of a cancer stem cell (CSC) phenotype in solid tumors has greatly enhanced the understanding of the mechanisms responsible for cancer cell metastasis. In keeping with Pagets 'seed and soil' theory, CSCs display dependence upon stromal derived factors found within the niche in which they reside. Inflammatory mediators act as a 'fertilizer' within this niche when interacting with CSCs at the tumor–stromal interface and can potentiate the metastatic ability of CSCs. Interestingly, the same components of the pro-inflammatory milieu experienced by cancer patients perioperatively are known to promote the metastagenic potential of CSCs. On the basis of this observation we discuss how surgery-induced inflammation potentiates colon CSC involvement in the metastatic process. We hypothesize that the high rates of recurrence and metastasis associated with tumor resection are potentiated by the effects of surgery-induced inflammation on CSCs. Finally we discuss potential therapeutic strategies for use in the perioperative window to protect cancer patients from the oncological effects of the pro-inflammatory milieu.